Peningkatan Hasil Belajar Siswa Menggunakan Metode Index Card Match di UPTD SDN 03 Koto Baru Simalanggang - Rahmi Husni; Iswantir Iswantir; Defi Yuslia; Imelda Sofia; Wirna Wirna; Aprinaldi Aprinaldi (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Education aims to improve the quantity and quality of students. In the learning process, the selection of the right learning method greatly affects the high and low learning outcomes of students. Learning methods are ways that can be done by educators so that the teaching and learning process runs effectively. The problem in this study is the low learning outcomes of students in the subject of Islamic Religious Education. because the learning methods used are still not varied enough. To overcome this problem, the researcher applied the Index Card Match method with the aim of improving Islamic Religious Education learning outcomes for students at UPTD SD Negeri 03 Koto Baru Simalanggang. This study uses a type of classroom action research (CAR). The subjects in this study were students in the class at UPTD SD Negeri 03 Koto Baru Simalanggang, totaling 18 students consisting of 12 male students and 6 female students. Classroom action research was carried out in two cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and written tests. Based on the results of the study, it showed that the average learning outcomes of students increased. It is known that the KKM value that has been determined by the school is 75. In the pre-research, it was known that 3 students had not completed it with a percentage of 30% and 7 students had completed it with a percentage of 70%. In cycle I, there was an increase of 6 students who completed it with a percentage of 60% and 4 students who had not completed it with a percentage of 40%. Furthermore, in cycle II, there was an increase of 9 students with a percentage of 90% and 1 student who had not completed it with a percentage of 10%. Thus, the Index Card Match method can improve student learning outcomes in the PAI subject at UPTD SD Negeri 03 Koto Baru Simalanggang